Pengaruh Audit Internal, Efektivitas Komite Audit, Dan Pengendalian Internal Terhadap Pencegahan Fraud Pada Bank BUMN Di Batam - Anggiena, Anggiena; Prima, Argo Putra (LPPM Universitas Putera Batam, 2024)
Not a few cases of fraud that occur in state-owned banks due to the weak internal role of their companies. This study was conducted to determine the effect of internal audit, audit committee effectiveness, and internal control on fraud prevention. The method of data analysis carried out is by distributing questionnaires to bank employees consisting of employees who work in the field of operations, credit, and technology and information. This research uses a quantitative approach. The data analysis technique uses multiple linear regression analysis, t-test, F test, and determination coefficient test (R2) and uses classical assumption tests, namely normality test, multicollinearity test, and heteroscedasticity test. Based on the t-test, internal audit has a positive effect on fraud prevention at BUMN Banks in Batam, the effectiveness of the audit committee has a positive effect on fraud prevention at BUMN Banks in Batam, and internal control has no effect on fraud prevention at BUMN Banks in Batam. Based on the F hypothesis test, internal audit, audit committee effectiveness, and internal control significantly positively affect fraud prevention at BUMN Banks in Batam. Keywords: Internal Audit; Audit Committee Efectiveness; Internal Control; Fraud Prevention.